In Silico Study of Bioactive Compounds in Herba Sambiloto (Andrographis paniculata Burm. F. Nees) as HIV-1 Reverse Transcriptase Inhibitor - Prasetiyo, Andri; Martati, Titiek; Saputra, Putri Windari (Tropical Biopharmaca Research Center, IPB University, 2024)
A medicinal plant known as sambiloto (Andrographis paniculata Burm. F. Nees) contains certain active compounds that potentially are anti-HIV. However, it is not yet known which compounds are involved in inhibiting HIV activity. This study aimed to identify potentially active compounds from the sambiloto plant that could inhibit the HIV-1 reverse transcriptase enzyme using the in-silico method. In silico methods that will be carried out are internal validation, molecular docking, ADMET prediction, and molecular dynamics. The molecular docking results showed that the five best compounds have potential as anti-HIV drugs compared to efavirenz with the rerank score -152.119 until -125.177 kcal/mol. In contrast, the rerank score of the comparison ligand is -94.7639 kcal/mol. The ADMET prediction showed that the selected compounds have a good pharmacokinetics profile and are nontoxic. The molecular dynamic results showed that deoxy-11,12-didehydroandrographiside and andropraphiside are stable and have potential as anti-HIV drugs with average RMSD values of 1.88 and 2.02 Å while the comparison ligand is 1.67 Å.